2012
DOI: 10.1364/oe.20.003268
|View full text |Cite
|
Sign up to set email alerts
|

High frequency optoelectronic oscillators based on the optical feedback of semiconductor mode-locked laser diodes

Abstract: Optical self seeding feedback techniques can be used to improve the noise characteristics of passively mode-locked laser diodes. External cavities such as fiber optic cables can increase the memory of the phase and subsequently improve the timing jitter. In this work, an improved optical feedback architecture is proposed using an optical fiber loop delay as a cavity extension of the mode-locked laser. We investigate the effect of the noise reduction as a function of the loop length and feedback power. The well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Reduction in timing jitter occurs due to suppression of external cavity side-modes relative to single-loop feedback. In the literature [13,14], it was experimentally observed that side-mode suppression was achieved when both feedback delays had a common multiple. This shows that effective suppression in external cavity side-modes is highly dependent on the length of the second loop.…”
Section: Lettermentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction in timing jitter occurs due to suppression of external cavity side-modes relative to single-loop feedback. In the literature [13,14], it was experimentally observed that side-mode suppression was achieved when both feedback delays had a common multiple. This shows that effective suppression in external cavity side-modes is highly dependent on the length of the second loop.…”
Section: Lettermentioning
confidence: 99%
“…A major limitation of MLLs for most practical applications is their very high timing jitter and phase noise, as spontaneous emission noise and cavity losses make MLLs prone to broad linewidths and, therefore, substantial phase noise [4]. To improve the timing jitter, several experimental methods such as single-cavity feedback [5][6][7][8], coupled optoelectronic oscillators [9], injection locking [10][11][12], and dual-loop feedback [13][14][15] have been proposed and demonstrated. Of the stabilization techniques demonstrated to date, optical feedback is a promising approach in which an additional reflector creates a compound cavity with a high quality factor, with no need for an external radio frequency (RF) or optical source.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting phase noise is just above −110 dBc/Hz at a 1 Hz offset. Other OEOs have also been demonstrated using optical injection locking of lasers to generate the RF tone [65]. …”
Section: Oeo With Other Optical Modulatorsmentioning
confidence: 99%
“…This dual loop feedback configuration gives sub-kHz linewidth with 38 dB suppression in the fundamental side-mode. A number of experimental [18][19][20][21] and numerical investigations [22] have also been made of the dynamics of modelocked semiconductor lasers subject to dual loop feedback. We note that optimum performance of RF linewidth and timing jitter in dual loop feedback has been very sensitive to small phase adjustments, which limits operation to a narrow parameter space and makes optimum performance vulnerable to environmental change.…”
Section: Introductionmentioning
confidence: 99%